2004
DOI: 10.1097/00004872-200410000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase, catalase and glutathione peroxidase in the spontaneously hypertensive rat kidney

Abstract: Oxidative stress in SHR was associated with a lack of coordinate upregulation of the antioxidant enzymes and discordance between their protein abundance and enzymatic activity. These findings suggest an impaired antioxidant defense system and the presence of functionally abnormal enzymes in the SHR kidney. Lifelong antioxidant therapy improved expression, activity and activity-to-mass relationship of the measured enzymes. The latter suggests oxidative and nitrosative modification of these molecules in the SHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 28 publications
5
76
1
1
Order By: Relevance
“…70 The decrease in enzymatic antioxidant activity in hypertensive humans and in animal models of hypertension has been widely reported, which suggests that reduced antioxidant defenses are involved in this disease. [71][72][73][74][75][76] Another endogenous antioxidant is glutathione, which displays direct antioxidant activity by providing the hydrogen at the sulfur atom to transform a free radical into a stable molecule. 77 An impairment of the glutathione system in hypertension has been demonstrated.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…70 The decrease in enzymatic antioxidant activity in hypertensive humans and in animal models of hypertension has been widely reported, which suggests that reduced antioxidant defenses are involved in this disease. [71][72][73][74][75][76] Another endogenous antioxidant is glutathione, which displays direct antioxidant activity by providing the hydrogen at the sulfur atom to transform a free radical into a stable molecule. 77 An impairment of the glutathione system in hypertension has been demonstrated.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…156 In a Mediterranean population with an elevated fat consumption, a high fruit and vegetable intake is inversely associated with blood pressure levels. 157 Short-term studies indicated that specialized diets may prevent or ameliorate mild hypertension; most notable are the Dietary Approaches to Stop Hypertension ROS scavenging 65,103 Iron chelation 65,103 Enzyme modulation 65,103 Allopurinol Inhibition of xanthine oxidase [75][76][77] Figure 2 Schematic summary of the exogenous antioxidant mechanisms likely accounting for anti-hypertensive effects. NO, nitric oxide; eNOS, nitric oxide synthase; ROS, reactive oxygen species; BH 4 , tetrahydrobiopterin; oxBH4, oxidized tetrahydrobiopterin; NAC, N-acetylcysteine; VSMC, vascular smooth muscle cells.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…Inhibition of NAD(P)H oxidase activity by gp91ds-tat, a chimeric peptide that inhibits p47 phox association with gp91 phox in NAD(P)H oxidase, attenuates blood pressure increase, regresses cardiac and vascular remodeling and improves endothelial function in ANG II-infused rodents, as does apocynin [20,78]. The increased collagen volume fraction of the ventricles of aldosterone-treated rats is also prevented by cotreatment with the antioxidant N-acetyl cysteine or pyrolidine dithiocarbamate which also abrogates the aldosterone-induced NAD(P)H oxidase and NF-κB activation [79].…”
Section: Ang Ii-induced Collagen Production and Degradation During Inmentioning
confidence: 99%
“…In mammalian tissue three isoforms of SOD have been identified and differ in their location. Cu/Zn-SOD constitutes 90% of total tissue [20] and is localized in the cytosol, Mn-SOD in the mitochondria and extracellular SOD in the interstitial fluid [21]. Inhibition of endogenous SOD by the specific inhibitor diethyldithiocarbamic acid (DETC), a copper chelator, increases basal O 2 -production in aorta rings of normal and spontaneously hypertensive rats [22] and in rings of rabbit thoracic aorta [23].…”
Section: Introductionmentioning
confidence: 99%
“…Tal fato pode ser explicado, pois ambas as enzimas competem pelo mesmo substrato (peróxido de hidrogênio). De fato, os resultados em relação às enzimas antioxidantes parecem ainda não estar muito claros no presente estudo, fazendo com que seja necessário avaliar outros marcadores de EO para melhor interpretação (ZHAN et al, 2004;FORTEPIANI & RECKELHOFF, 2005). Neste sentido, a avaliação da capacidade antioxidante não enzimática poderia favorecer o entendimento da redução de parâmetros de lesão relacionados ao estresse oxidativo nos grupos submetidos ao treinamento físico.…”
Section: Vfc Representa Um Mau Prognóstico (Ribeiro and Moraes Filho 2unclassified